Exploring EFL Junior High School Students’ Experiences in Learning English Pronunciation through Maher Zain’S Songs - Diva Kartika; Zainuddin; Feri Ferdiyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Pronunciation is an important aspect of English learning because it helps students communicate clearly. However, many EFL students still face difficulties in pronunciation due to limited exposure to authentic English input. This study aimed to explore junior high school students’ experiences in learning English pronunciation through Maher Zain’s songs. This study employed a qualitative descriptive design involving eighth-grade students of SMP Plus Tahdzibun Nasyiin. The participants were selected using purposive sampling. Data were collected through observation, interviews, and documentation and analyzed using Miles and Huberman’s interactive model. The findings revealed that students had positive learning experiences when learning pronunciation through Maher Zain’s songs. The songs helped students improve pronunciation accuracy, stress, intonation, and confidence. However, students also faced challenges such as fast song tempo and unfamiliar vocabulary. This study concludes that Maher Zain’s songs can be used as an effective medium for teaching pronunciation. Keywords: English songs, Maher Zain songs, Pronunciation, Students’ Experiences